(untitled) (Research, Society and Development, 2020)
This study carried out a scientometric approach on the bioactivity of bryophytes against insects and generated panoramas regarding the promising biotechnological techniques for this line of research, in world. Academic-scientific productions related to the theme, from 2000 to 2020, and on the news and perspectives in briotechnology for the control of insects were searched in virtual databases. Quantitative data were tabulated and analyzed in frequencies, using the Excel 2018 software, being represented in the form of tables and graphs, and the qualitative information in tables. Nineteen works (16 articles, two scientific notes and a chapter in e-book) were mapped, dispersed between the continents (except Antarctica) and between the years, with greater Asian production in 2012-2013. Sixteen hepatic species (10 botanical families) and 38 moss species (23 families) were identified, whose bioactivity was evaluated using extracts or plants in natura against lepidopterans, dipterans or coleopterans, with satisfactory results for antifeedant and/or insecticide and/or development inhibitor. The listed manuscripts were published in 15 journals of different impact factors, when there was, and one was in an e-book, usually with restricted access. The total number of citations these works was 255, especially in research not related to the subject in question. Techniques of genetic engineering, in vitro cultivation and cryopreservation of bryophytes are cited as current technologies that can support the bioprospecting of avascular plants on a commercial and sustainable scale. In the world there is few research on the relation of the insect-bryophyte that currently can serve for the development of natural agricultural pesticides. Therefore, it is necessary to expand the bioprospecting of bryoflora due to its biotechnological potential in pest control combined with biotechnology techniques that can boost commercial and sustainable production of pesticides bryophyte base or contribute to the improvement of agricultural plants.